HUBUNGAN ANTARA AKTIVITAS FISIK, POLA MAKAN, DAN OBESITAS DENGAN HIPERTENSI PADA REMAJA DI POSYANDU DESA TANJUNG - Salsabella Wahyuning Tyas; Rusnoto, Rusnoto; Tri Suwarto (Nusantara Hasana Journal, 2026)
Hypertension is a condition in which blood pressure increases abnormally during several examinations. In Blora Regency, 31.5% of the population aged 15 years and above suffer from hypertension, with a higher proportion in women than men. This study analyzed the relationship between physical activity, diet, and obesity, with hypertension in adolescents at the Tanjung Village Integrated Health Post (Posyandu). The study design used correlation analysis with a cross-sectional approach. The independent variables were physical activity, diet, and obesity while the dependent variable was hypertension. This study was conducted at the Tanjung Village Integrated Health Post (Posyandu) from September to October 2025. The number of samples of 44 adolescents was determined through random sampling selected randomly from the entire population. Data were collected using several research instruments, namely a questionnaire to measure adolescent physical activity based on the International Physical Activity Questionnaire (IPAQ) guidelines, a dietary questionnaire using the Food Frequency Questionnaire (FFQ), measurement of body mass index (BMI) by measuring weight and height of adolescents, and measurement of blood pressure using a digital sphygmomanometer. Data analysis used the chi-square test. There is a significant relationship between the level of physical activity and the incidence of hypertension in adolescents with a p-value of 0.0001 (p < 0.05). The research hypothesis is accepted with a positive relationship, which means the lower a person’s physical activity, the higher the risk of experiencing hypertension. There is a significant relationship between dietary patterns and the incidence of hypertension in adolescents with a p-value of 0.0001 (p < 0.05). Adolescents with poor dietary patterns (high sodium and low fiber) have a greater tendency to experience increased blood pressure. The majority of respondents with hypertension (26 out of 28 people) have a diet that is classified as unhealthy. There is a significant relationship between obesity status and the incidence of hypertension in adolescents with a p-value of 0.007 (p < 0.05). Obese respondents have a much higher probability of experiencing hypertension, where 13 out of 14 obese respondents were diagnosed with hypertension.